2011
DOI: 10.1016/j.ejpain.2011.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Review: Can we identify how programmes aimed at promoting self‐management in musculoskeletal pain work and who benefits? A systematic review of sub‐group analysis within RCTs

Abstract: The current evidence suggests four factors that relate to outcome as predictors/mediators, but there is no evidence for effect moderators. Future studies of mediation and moderation should be designed with 'a priori' hypotheses and adequate statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 41 publications
4
95
1
2
Order By: Relevance
“…Our findings about treatment expectations also concur with earlier work [30][31][32]. A systematic review of factors that influenced outcome from self-management programmes for chronic musculoskeletal pain found that self-efficacy, depression, pain catastrophising and physical activity were important [33].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings about treatment expectations also concur with earlier work [30][31][32]. A systematic review of factors that influenced outcome from self-management programmes for chronic musculoskeletal pain found that self-efficacy, depression, pain catastrophising and physical activity were important [33].…”
Section: Discussionsupporting
confidence: 90%
“…Although our data were cross sectional, our conclusion is consistent with findings of longitudinal research involving younger persons and demonstrating that these variables are predictive of future adjustment to pain (Miles et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…One potential benefit of active patient management is improved self-efficacy, which has been linked to positive outcomes for treatment of musculoskeletal conditions. 21 An often-mentioned threshold for good adherence to an eccentric-exercise regimen is above 75% of the total desired exercise volume (eg, 135 of 180 repetitions). 10,26,28 In our study, the standardregimen group achieved a mean exercise volume that was above this threshold.…”
Section: Eccentric-exercise Loadmentioning
confidence: 99%